Applying risk assessment approach to evaluate small island status in Kepulauan Seribu. Issue 1 (January 2022) - Ambo, S W; Yonvitner,; Samosir, A M
Abstract: Kepulauan Seribu with all potential need to be realized in an integrated management of coastal and ocean areas for sustainable development. The process of developing small islands in an integrated manner in the three islands needs to consider the risks that will occur. The purpose of this study is to analyze the level of risk in small islands and estimate the appropriate management of small islands for the Thousand Islands area. The method used in this study is a survey and observation method with an analysis of the IPCC (2014) model. The type of hazard that has the most potential to cause a disaster is a hurricane. The level of vulnerability in Harapan Island, Kelapa Island, and Kelapa Dua Island is relatively low, because there is only one hazard that has the potential to be a disaster, namely a tornado with a large enough magnitude and loss. The level of capacity owned by the three islands is quite good, so that the risk value in Harapan Island is 0.69, Kelapa Island is 0.68, and Kelapa Dua Island is 0.62 which is included in the low category.